Architectural Features of the First Period (13th-15th Century) Tekkes in the Balkan - Ammar Ibrahimgil (Science, Engineering and Technology, 2023)
Islamic religion spreading was influenced by the different local traditions among which Sufism, a religious mysticism (tasavvuf) organized under the institutions of tariqa emerged. This was followed by the emergence of as a place where divisions (orders) members were gathered known under names of tekke, zaviye, hankâh, ribat and a dervish lodge. This study elaborates several tekkes established by the Ottomans in the Balkans. Building style of the tekkes varied according to the procedures as well as manners of the order. Tekkes, which have a simple appearance, generally consist of a mosque, semahane, cellar, kitchen, cells, çilehane, selâmlık and harem. However, most of the buildings within the tekke are constructed over a large span of time. The aim of this study is to better understand the spatial setup of this organizational structure, which directly contributed to the conquest in the Balkans through the janissary corps and to the futuwwa (a set of religious and moral vocational norms) through the ahis (religious and moral vocational chamber). For this purpose, the locations of the tekkes and their architectural features, which were established successively one after the other with the conquests, have been analyzed. In final, the architectural typological of the tekkes is obtained according to the belief tradition, positioning, foundation schemes and special plans of the early period structures set within the tekke.